Patterning two-dimensional free-standing surfaces with mesoporous conducting polymers - Liu, Shaohua; Gordiichuk, Pavlo; Wu, Zhong-Shuai; Liu, Zhaoyang; Wei, Wei; Wagner, Manfred; Mohamed-Noriega, Nasser; Wu, Dongqing; Mai, Yiyong; Herrmann, Andreas; Muellen, Klaus; Feng, Xinliang (Nature Communications, 2015)
The ability to pattern functional moieties with well-defined architectures is highly important in material science, nanotechnology and bioengineering. Although two-dimensional surfaces can serve as attractive platforms, direct patterning them in solution with regular arrays remains a major challenge. Here we develop a versatile route to pattern two-dimensional free-standing surfaces in a controlled manner assisted by monomicelle close-packing assembly of block copolymers, which is unambiguously revealed by direct visual observation. This strategy allows for bottom-up patterning of polypyrrole and polyaniline with adjustable mesopores on various functional free-standing surfaces, including two-dimensional graphene, molybdenum sulfide, titania nanosheets and even on one-dimensional carbon nanotubes. As exemplified by graphene oxide-based mesoporous polypyrrole nanosheets, the unique sandwich structure with adjustable pore sizes (5-20 nm) and thickness (35-45 nm) as well as enlarged specific surface area (85 m 2 g a '1) provides excellent specific capacitance and rate performance for supercapacitors. Therefore, this approach will shed light on developing solution-based soft patterning of given interfaces towards bespoke functions.
CRIS-Team Scopus Importer:2023-03-20